Corrections to the Library of America Edition of Stevens's Poetry. - Serio, John N. (Wallace Stevens Journal)
The article reports that Wallace Stevens was not always served by his publisher. Topics include examines Milton J. Bates expanded Opus Posthumous by adding uncollected pieces, full sequences and the more recently discovered typescript of "From the Journal of Crispin"; and considered he also silently corrected misspellings and errors.